A Comparative Analysis Power Losses At The Connection Point Of Tap Connectors With Joint Press Connectors On Low Voltage Network East Binjai Customer Service Unit (ULP) - Mira Yolanda Br Sembiring; Dicky Lesmana; Zulkarnain Lubis (Jurnal Scientia, 2024)
In the electric power distribution network or a condition where a distribution system in the distribution of electric power experiences high power losses due to the connection point on the distribution cable to the consumer. Therefore, in this study, a calculation will be carried out between the value of the comparison of the input and output measurements between the connection points using Tap Connector with Joint Press Connector, after obtaining the measurement results, determine the calculation results for the loss of electrical power energy in rupiah units. A Tap Connector Joint Press Connector. After the measurement and calculation, the Power Loss is the result of the calculation between the input and output at the Tap Connector connection point. There is a difference in Power Loss of 134.3 Watts while at the Joint Press Connector the Power Loss Difference is 0 Watts. Power Loss Calculation Results in Rupiah Units From the results of the power loss analysis calculation, it can be seen that the power loss at the Tap Connector connection point with a difference in power loss value of 134.3 W and if calculated in rupiah units, then the loss of electrical energy in one month is Rp. 130,539.6, -. If it occurs in one year in a 24-hour time calculation, it is 130,539.6 x 12 Months = 1,566,475.2, -. The cause of power loss at the Tap Connector connection point is due to poor installation, as well as Tap Connector Equipment that is not SPLN standard and the age of the Tap Connector that has worn out